Digital Transformation, Human Capital Upgrading, FDI Spillover and Green Total Factor Productivity: Evidence from Vietnamese Provinces - Nguyen, Thuy Trang; Phung, Mai Lan (International Journal of Energy Economics and Policy, 2025)
The study examines the relationship between FDI spillover and green total factor productivity (GTFP) at the provincial level, as well as exploring the roles of digital transformation and human capital upgrading in this relationship using the global Malmquist-Luenberger index, system generalized methods of moments (S-GMM) combined with threshold model. Using a panel data from 63 Vietnamese provinces from 2011 to 2022, the research findings show that the FDI spillover has contributed significantly to province-level GTFP enhancement and both digital transformation, human capital upgrading positively moderate the effect of FDI spillover on provincial GTFP. Besides, the positive influence of FDI spillover on GTFP has a significant double threshold effect when advanced human capital is used as the threshold variable. These findings emphasize the significance of encouraging FDI spillover, enhancing digital transformation, and strengthening high-quality human capital as viable strategies for improving GTFP.